Menatapi Senyom Simpol; Campur Kode Bahasa Melayu Pontianak Ragam Tulis di Media Massa - Evi Novianti; NFN Irmayani (tuahtalino, 2016)
The Malay Pontianak on a variety of writing is very rare. This language has similarities with Indonesian. This fact leads to code-mixing. This study discusses the code-mixing in the Senyom Simpol rubric. The approach used in this research is sociolinguistic. The method used is quantitative descriptive. The theory used in the analysis is the theory of code-mixing and code switching expressed by Sumarsono (2007), Thelander (2004), Appel (1979), Fishman (2007) and several other experts. The conclusion is code-mixing that occurs within the rubric Senyom Simpol occur at the level of grapheme, morpheme, phrase, clause, and sentence. The causes of code-mixing is the author are not native speakers of Malay Pontianak.